(Adult) education in the perspective of emotional geography. Towards a transdisciplinary approach in andragogy research - Góralska, Renata (Rocznik Andragogiczny, 2023)
The aim of the article is to describe emotional geography, i.e. a research trend located on the borderline between human geography and contemporary affect studies, which focuses on the relationship between emotions and the broadly understood environmental, socio-cultural, spatial, economic, and political context. For this purpose, the author refers to theoretical analyses and research in the area of the so-called affective turn, and to the critical and political theories of emotions. She presents the relationship between education and emotional geography as well as examples of educational research projects on the socio-cultural spatial analyses of emotions and education. She also indicates the methodological implications for educational and andragogy research projects concerning the study of emotions in education, i.e. their transdisciplinary dimension. The presented way of conceptualizing the emotional geography of (in) education is a new look at the functioning of educational institutions and at the practice of lifelong learning. It can be a source of empirical research projects for theorists of education and andragogues.